(untitled) (Research, Society and Development, 2022)
The present study aimed to discuss inclusive educational policies and how they reach high school students with intellectual disabilities in SEDUC/AM schools, taking as a reference their implementation from the investigated schools. Methodologically, the study has a qualitative nature of documental, bibliographic and field analysis, focusing on the dialectical method, and for its accomplishment we used the semi-structured interview. Initially, categories were created that were later analyzed from the answers extracted from the interview script using Bardin’s content analysis (1977; 2011). Institutional managers who, within their functions, organize, delegate and collaborate in the implementation of programs, projects and actions, of federal or state competence, in state high schools participated in the study. As main results, we verified that educational policies, through programs, projects and actions, developed for the high school public, in Manaus/AM, are reaching schools to serve all students, which does not mean if they are reaching the student with DI and promoting significant changes in their schooling process. The school’s challenge lies in complying with the principles of inclusion, avoiding the maintenance of homogeneous pedagogical practice, framing the student with ID in universal didactic procedures, disregarding differences. Through the Accessible School Program (PEA) it is possible to restructure the schools that adhere to the PEA in terms of infrastructure, with resources made available to those covered by the Program for the Implementation of Multifunctional Resource Rooms (SRM) and the Specialized Educational Assistance (AEE) for students with ID or other deficiencies. Keywords: Education; Teaching; Intellectual disability; Amazonas.